Adolessente dogters moet voorligting oor die ondersoek van die mamma en menstruasie kry - A Ferreira (AOSIS, 1985)
Due to the anatomical and physiological changes which take place during puberty the adolescent girl is very aware of her own body. Therefore, puberty is the ideal time for teaching her about menstruation and self-examination of the breast. In this study it was found that a group of adolescent girls did not have enough information about these two subjects. It was found that the nurse has an important role in this regard because she is equipped to give the necessary information to both parents and their daughters.